2018
DOI: 10.1002/zamm.201800022
|View full text |Cite
|
Sign up to set email alerts
|

Higher order couple stress theory of plates and shells

Abstract: New higher order models of the couple stress plates and shells have been developed here. The 3-D equations of the linear couple stress elasticity have been presented in an orthogonal system of coordinates. For the creation of 2-D models of plates and shells the curvilinear system of coordinates related to the middle surface of the shell has been used along with a special hypothesis based on assumptions that consider the fact that the considered plates and shells are thin. Higher order theory is based on the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 94 publications
(131 reference statements)
0
12
0
1
Order By: Relevance
“…Many experimental observations have shown that the micro/nano structures, which have been widely used in modern engineering applications, may experience size‐dependent mechanical behaviors. Various non‐classical higher‐order continuum theories, such as the strain gradient theory (SGT) and the couple stress theory (CST), have been developed for describing such size‐dependent phenomena . However, as these higher‐order theories are more complex than the classical one, the analytical or semi‐analytical solutions are available only for restricted problems with simple geometries and certain boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental observations have shown that the micro/nano structures, which have been widely used in modern engineering applications, may experience size‐dependent mechanical behaviors. Various non‐classical higher‐order continuum theories, such as the strain gradient theory (SGT) and the couple stress theory (CST), have been developed for describing such size‐dependent phenomena . However, as these higher‐order theories are more complex than the classical one, the analytical or semi‐analytical solutions are available only for restricted problems with simple geometries and certain boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[48] investigated chaotic vibrations of nanoshells with circular planforms. A new higher order plate and shell theories were developed by Zozulya [49], based on couple stress elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, many CST/SGT‐based beam [25–39] and plate [40–54] models have been established to investigate the dynamic and static problems of homogeneous/FG micro‐components. Within the gradient elasticity framework, micro‐stiffness/micro‐inertia effects in small‐scale structures [26, 8], non‐physical stress singularity at crack tips [23], and abnormal wave propagation behavior in second gradient solids [19, 55, 56] can be accounted for.…”
Section: Introductionmentioning
confidence: 99%